2017
DOI: 10.1515/jtim-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Protracted inhibition of vascular endothelial growth factor signaling improves survival in metastatic colorectal cancer: A systematic review

Abstract: Clinical data suggest that beyond-progression, the blockade of angiogenesis is associated with improved survivals in colorectal cancer. We conducted a systematic review to investigate the therapeutic effects of antiangiogenic drugs administered as later lines of treatment in patients already progressed to a previous anti-VEGF based treatment. An extensive literature search was conducted. Hazard ratios (HR) for progression (PFS) and death (OS) were extracted. An inverse-variance meta-analysis model was implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…It is closely related to lymphangiogenesis in gastric or other cancers[32,33]. VEGF-C is an important lymphangiogenic factor and plays an important role in lymphangiogenesis[34,35]. Our study found that expression of VEGF-C protein in gastric cancer cells decreased 48 h after transfection of LSD-shRNA interference plasmid, suggesting that downregulation of LSD1 expression inhibits tumor metastasis by inhibiting VEGF-C expression.…”
Section: Discussionmentioning
confidence: 62%
“…It is closely related to lymphangiogenesis in gastric or other cancers[32,33]. VEGF-C is an important lymphangiogenic factor and plays an important role in lymphangiogenesis[34,35]. Our study found that expression of VEGF-C protein in gastric cancer cells decreased 48 h after transfection of LSD-shRNA interference plasmid, suggesting that downregulation of LSD1 expression inhibits tumor metastasis by inhibiting VEGF-C expression.…”
Section: Discussionmentioning
confidence: 62%
“…There is no accurate and efficient clinical biomarker of GC. Other gastrointestinal biomarkers or early detection methods were also not applied in GC[26-28]. Therefore, the aim of our study was to investigate whether LOX and HIF1α could be used as biomarkers of GC.…”
Section: Discussionmentioning
confidence: 99%
“…Statistics on cancer-related deaths show that lung cancer accounts for 25% of male and 15% of female deaths. It is the first leading cause of cancer death in men and the second leading cause in women [ 1 – 5 ]. According to histological classification, lung cancer is divided into two types: non-small cell lung cancer (NSCLC) and small cell lung cancer [ 6 ].…”
Section: Introductionmentioning
confidence: 99%